2020
DOI: 10.1177/0003702820940391
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Fluctuations in Surface-Enhanced Raman Scattering Intensities from Various Nanostructures

Abstract: The observation of single molecule events using surface-enhanced Raman scattering (SERS) is a well-established phenomenon. These events are characterized by strong fluctuations in SERS intensities. High-speed SERS intensity fluctuations (in the microsecond time scale) have been reported for experiments involving single metallic particles. In this work, the high-speed SERS behavior of six different types of nanostructured metal systems (Ag nanoshells, Ag nanostars, Ag aggregated spheres, Au aggregated spheres, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In some occasions, the Stokes-shifted SIF activities were seen to originate from different locations at different times for each of the excitation colors. Similarly, experiments performed using two different polarizations (perpendicular to each other) also revealed selective excitation of different areas on a single particle, suggesting that the excitation conditions for individual hotspot environments were accessed.…”
Section: Ultrahigh Speed Sersmentioning
confidence: 86%
See 1 more Smart Citation
“…In some occasions, the Stokes-shifted SIF activities were seen to originate from different locations at different times for each of the excitation colors. Similarly, experiments performed using two different polarizations (perpendicular to each other) also revealed selective excitation of different areas on a single particle, suggesting that the excitation conditions for individual hotspot environments were accessed.…”
Section: Ultrahigh Speed Sersmentioning
confidence: 86%
“…In some occasions, the Stokes-shifted SIF activities were seen to originate from different locations at different times for each of the excitation colors. Similarly, experiments performed using two different polarizations (perpendicular to each other) also revealed selective excitation of different areas on a single particle, 39 suggesting that the excitation conditions for individual hotspot environments were accessed. The statistics of the time dependent SIFs presented in Figures 3 and 4 seems to imply that hotspots are turned on (and off) in very localized regions on the single nanoparticle, which allow single molecule events to be observed even from a fully coated surface.…”
Section: ■ Ultrahigh Speed Sersmentioning
confidence: 94%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms ( 8 , 9 ). Single-molecule experimentation allows fluctuation analysis ( 10–12 ) and has revealed very heterogeneous behavior of molecules ( 13–18 ). Measurements have shown that protein-mediated loops form and rupture stochastically, and the lifetimes of such loops span several orders of magnitude ( 19–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms (Nelson, 2003;Phillips R. et al, 2013). Single-molecule experimentation allows fluctuation analysis (Bido et al;Kundu et al, 2020;Milenkovic et al, 2020) and has revealed the robustly heterogeneous looping behavior of molecules (Datta and Seed, 2018;Finzi and Gelles, 1995;Graham et al, 2017;Kumar et al, 2016;Manzo et al, 2011;Manzo et al, 2012;Miyashita et al, 2015;Neuman et al, 2003;Wang et al, 1998;Zurla, 2009). Indeed, protein-mediated loops form and rupture stochastically in purified systems, and the lifetimes of such loops span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms (6,7). Single-molecule experimentation allows fluctuation analysis (8)(9)(10) and has revealed very heterogeneous looping behavior of molecules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Measurements have shown that protein-mediated loops form and rupture stochastically, and the lifetimes of such loops span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%